The design and use of a simple device for the MRI assessment of changes in cardiovascular function by lower-body negative-pressure-simulated reduction of central blood volume. Issue 6 (June 2021) - Hamilton, M.C.K.; Neumann, S.; Szantho, G.; Rydon, L.; Lawton, C.B.; Hart, E.; Manghat, N.E.; Turner, M.S.
Abstract : AIM: To use a locally designed and simple lower-body negative-pressure (LBNP) device and 1.5 T magnetic resonance imaging (MRI) to demonstrate the ability to assess changes in cardiovascular function during preload reduction. These effects were evaluated on ventricular volumes and great vessel flow in healthy volunteers, for which there are limited published data. MATERIAL AND METHODS: After ethical review, 14 volunteers (mean age 33.9 ± 7 years, mean body mass index [BMI] 23.1 ± 2.5) underwent LBNP prospectively at 0, –5, –10, and –20 mmHg pressure, using a locally designed LBNP box. Expiratory breath-hold biventricular volumes, and free-breathing flow imaging of the ascending aorta and main pulmonary artery were acquired at each level of LBNP. RESULTS: At –5 mmHg, there was no change in aortic flow or left ventricular volumes versus baseline. Right ventricular output ( p= 0.013) and pulmonary net flow ( p= 0.026) decreased. At –20 mmHg, aortic and pulmonary net flow ( p< 0.001) decreased, as were left and right ventricular end diastolic volume ( p< 0.001) and left and right end systolic volumes ( p= 0.038 and p= 0.003 respectively). CONCLUSIONS: Use of a MRI-compatible LBNP device is feasible to measure changes in ventricular volume and great arterial flow in the same experiment. This may enhance further research into the effects of preload reduction by MRI in a wide range of important cardiovascular pathologies. Highlights: An MRI compatible lower body negative pressure (LBNP) device can be implemented. Allowing enhanced research into the effects of preload reduction. Applicable to a wide variety of cardiac conditions.